Identification of Pseudomonas aeruginosa from post-traumatic wounds in Dhaka and their antimicrobial susceptibility profiles: a single-center cross-sectional study - Drishti, Deblina Das; Shithi, Alvia Amin; Faria, Zareen Tasnim (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2024.